COTTON FIBER RATING, INNOVATION CURRENT DEVELOPMENTS, PROSPECTS FOR COOPERATION OF FARMS AND CLUSTERS - Abdullayev, Ravshan (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article shows the results of six varieties of cotton seed breeding varieties grown by supplying them with high yields with advanced agrotechnical methods, production of high-quality cotton fiber from cultivated raw cotton, introduction of new technologies, as well as the classification of the resulting cotton fiber based on the international universal ISO standard, as well as conducted scientific and practical research in determining the rating place of the fiber.